2021
DOI: 10.1093/jn/nxab313
|View full text |Cite
|
Sign up to set email alerts
|

Proposed Anti-Inflammatory Diet Reduces Inflammation in Compliant, Weight-Stable Patients with Rheumatoid Arthritis in a Randomized Controlled Crossover Trial

Abstract: Background It is unclear to what extent adjuvant dietary intervention can influence inflammation in rheumatoid arthritis (RA). Objectives The objective was to assess the effects of dietary manipulation on inflammation in patients with RA. Methods In a crossover design, participants [n = 50, 78% females, median BMI (in kg/m2) 27, median age 63 y] were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
(30 reference statements)
1
14
0
1
Order By: Relevance
“…Several studies have previously assessed the role of olive oil, olives, and nuts, alone or as components of the Mediterranean diet, in RA disease activity [ 20 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Except for one Iranian trial dealing with the efficacy of topical olive oil in controlling pain through skin absorption [ 42 ], the remaining trials considered a supplementary herbal formulation of olive oil, fig and olive fruits, together with routine DMARDs regimen (vs. routine DMARDs regimen alone) [ 43 ], or a combination of fish oil omega-3 fatty acids (3 grs/day) and 9.6 mL of olive oil (vs. fish oil omega-3 fatty acid (3 grs/day) or a soy oil placebo), in addition to the usual medication [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have previously assessed the role of olive oil, olives, and nuts, alone or as components of the Mediterranean diet, in RA disease activity [ 20 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Except for one Iranian trial dealing with the efficacy of topical olive oil in controlling pain through skin absorption [ 42 ], the remaining trials considered a supplementary herbal formulation of olive oil, fig and olive fruits, together with routine DMARDs regimen (vs. routine DMARDs regimen alone) [ 43 ], or a combination of fish oil omega-3 fatty acids (3 grs/day) and 9.6 mL of olive oil (vs. fish oil omega-3 fatty acid (3 grs/day) or a soy oil placebo), in addition to the usual medication [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no trials in humans have targeted nuts as foods rich in omega-3 fatty acids. Evidence may be still indirectly obtained from trials proposing a portfolio diet of anti-inflammatory foods (i.e., a high intake of fatty fish, whole grains, fruits, nuts, berries, and canola—but not olive—oil) [ 36 , 38 ] or a Mediterranean-like dietary pattern, where olive oil is traditionally consumed too [ 39 , 40 ]. In a cross-over trial, no significant difference in DAS28 was found between the proposed portfolio diet and a control diet similar to the general dietary intake in Sweden, although it was significantly lower after the intervention than after the control period in the participants who completed both periods [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, nutrition plays an important auxiliary role in the prevention and management of AIRDs [ 10 ]. A plethora of evidence has linked disease progression, severity, relapse and pharmacotherapy-induced adverse events to specific dietary interventions/changes [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Furthermore, the large majority of patients with AIRDs also demonstrate overweight and obesity, aggravated by physical inactivity [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intervention diets rich in EPA and DHA increased these fatty acids in both studies, and the fatty acid pattern changed significantly in erythrocytes and plasma. Despite this, the effects on inflammation markers were limited [ 21 , 22 ]. Because changes in pro and anti-inflammatory lipid mediators, such as oxylipins, precede changes in other inflammatory markers such as cytokines, it would be of value to establish if oxylipins changed in line with changed dietary fatty-acid intake.…”
Section: Introductionmentioning
confidence: 99%